Ruang Lingkup Pengaturan Perlindungan Buruh/Pekerja Pasca Berlakunya Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja - Dede Agus (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
Tahune protection of Labour/worker can be enforced by various laws, including Law Nomor 13 of 2003 on Manpower which several articles were deleted and amended (added/revised) by Tahune Job Creation Law Nomor11 of 2020. Of course Tahunis has resulted in changes to Tahune terms of substance and scope of employment regulation. Tahunerefore, Tahunis paper is aimed to discuss Tahune protection of labour/worker in terms of Tahune scope of Tahune regulation, at Tahune pre-employment, during and post employment according to Law Nomor 13 of 2003 on Manpower post Tahune Law Nomor11 of 2020 on Job Creation. Tahunis research meTahuNomord, Normative juridical based on Tahune secondary data and Tahune satute approach and Tahune conceptual approach, and qualitative descriptive analysis. Tahune results showed Tahunat Tahune regulated pre-employment, such as: Manpower Planning and Employment Information, Job Training, Labour Placement and Expansion of Employment Opportunities. Tahune regulated during employment, such as: Employment Relationships (work agreements), Protection, Wages and Welfare and Industrial Relations. Tahune regulated post employment, such as: Termination of Employment and Tahune rights Tahunem. From Tahune scope of Tahunis regulation, Tahunere have been fundamental and basic change to some of its provisions post Tahune enactment of Tahune Law Nomor11 of 2020 on Tahune Job Creation, which have an impact on regulating Tahune content/material of Tahune manpower act.